Sosialisasi dan Percepatan Penanggulangan Stunting Melalui Pemberian Makanan Tambahan pada Balita di Grogolan, Boyolali: (Socialization and Acceleration of Stunting Reduction by Providing Additional Food to Toddlers in Grogolan, Boyolali) - Amelia, Rizki Nor; Dewi, Evi Indah Kusuma; Saleh , Muhammad; Kurniawan, Tri Prasetyo Adam (Laboratorium Pembelajaran FKIP Universitas Jambi, 2025)
Stunting is one of the threats to human quality and is also considered a threat to the competitiveness of a nation. This community service aims to socialize the understanding of stunting and apply this understanding in the form of Providing Additional Food (PMT) to toddlers who are classified as and at risk of stunting. The method used in this activity is a combination approach of community education methods and diffusion of science and technology. After the socialization, 80% of respondents understood stunting well, 66.67% of respondents understood PMT well, and 60% of respondents understood the techniques of processing food ingredients to be used as additional food products or complementary foods for toddlers well. In the end, in general, the program from the UNNES GIAT 6 KKN team ran smoothly and successfully, as evidenced by the positive responses of the participants. Abstrak. Stunting menjadi salah satu ancaman terhadap kualitas manusia dan juga dianggap sebagai ancaman terhadap kemampuan daya saing suatu bangsa.Pengabdian kepada masyarakat ini bertujuan untuk mensosialisasikn pemahaman terhadap stunting dan mengaplikasikan pemahaman tersebut dalam bentuk Pemberian Makanan Tambahan (PMT) kepada balita yang tergolong dan berisiko stunting. Metode yang digunakan dalam kegiatan ini adalah pendekatan kombinasi dari metode pendidikan masyarakat dan difusi IPTEKS. Setelah dilakukan sosialisasi, 80% responden telah memahami stunting dengan baik, 66,67% responden memahami PMT dengan baik, dan 60% responden memahami teknik pengolahan bahan makanan untuk dijadikan produk makanan tambahan atau makanan pendamping bagi balita dengan baik. Pada akhirnya, secara umum program dari tim KKN UNNES GIAT 6 berjalan dengan lancar dan sukses yang dibuktikan dari respon positif peserta.